(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Wood machining through milling is one of the wide-used cutting processes in woodwork-ing and furniture industry. It is also one of the noisiest, due to the high noise immission levels that often exceed the accepted sanitary standards. In this work the influence of the feed rate, the speed of the working shaft (or cutting speed) and the thickness of the out cut layer on the noise levels, measured at work place, generated during Pinus silvestris L. milling process has been evaluated.